Effectiveness of progressive muscle relaxation therapy on reducing violent behavior in schizophrenia patients: a quasi-experimental study - Abdullah Abdullah; Abubakar Betan; Yanti Mustarin; Susi Susanti; Nur Ambiy (Jurnal Ilmiah Kesehatan Sandi Husada, 2026)
Introduction: Schizophrenia is a chronic mental disorder often associated with aggressive and violent behavior, which can negatively impact patient safety and quality of care. Non-pharmacological interventions such as progressive muscle relaxation (PMR) are increasingly used to manage behavioral symptoms. This study aimed to evaluate the effectiveness of PMR therapy in reducing violent behavior among schizophrenia patients. Research Methodology: This study employed a quantitative quasi-experimental design with a one-group pretest–posttest approach. The sample consisted of 29 schizophrenia patients with violent behavior selected using purposive sampling at a regional psychiatric hospital in South Sulawesi, Indonesia. Data were collected using an observation checklist. Statistical analysis was performed using the Wilcoxon signed-rank test to compare pre- and post-intervention scores. Results: The mean score of violent behavior significantly decreased from 7.86 (SD = 2.386) at pretest to 3.14 (SD = 1.156) at posttest. Statistical analysis showed a significant difference between pre- and post-intervention (p = 0.000; p < 0.05). These findings indicate that PMR therapy effectively reduces violent behavior in schizophrenia patients. Conclusion: Progressive muscle relaxation is an effective, safe, and practical non-pharmacological intervention to reduce violent behavior in schizophrenia patients. It can be integrated into psychiatric nursing care to improve emotional regulation and patient outcomes.